The Role of Teacher Training in Effective EFL Instruction in Mali and sub-Saharan Africa: A Systematic Literature Review - Haïdara, Youssouf (Universitas Islam Negeri Raden Intan Lampung, 2025)
This systematic literature review critically examines the role of teacher training in promoting effective English as a Foreign Language (EFL) instruction in Mali. Analyzing six peer-reviewed articles published between 2021 and 2025, the review synthesizes findings on general EFL instruction, prevalent challenges, the specific impact of teacher training, existing methodologies, and identified research gaps. The review reveals that despite global shifts towards an English as an International Language (EIL) approach and the recognized benefits of mother-tongue-mediated instruction for learning and cultural identity, Malian EFL instruction faces profound systemic and contextual challenges. Key impediments include inadequate teacher training, large class sizes, severe lack of appropriate teaching materials and technological infrastructure, low student proficiency, and motivational issues. Student diagnostic test results demonstrate particular weaknesses in applying and analyzing skills within EFL. Findings underscore that while a majority of Malian EFL teachers attend professional development sessions (e.g., 72% for CBA training ), a substantial proportion (94%) report persistent difficulties in implementing new approaches, often reverting to traditional methods due to a perceived lack of practical training and supportive resources. The critical impact of these challenges is evident in suboptimal student learning outcomes. The review highlights teachers' resourceful self-initiated solutions, such as peer collaboration and utilizing digital platforms like WhatsApp for professional development, yet these are also subject to contextual constraints like connectivity costs and digital literacy. The synthesis concludes that effective EFL instruction in Mali necessitates comprehensive, context-specific, and sustained teacher training programs that transcend theoretical knowledge to address practical classroom realities. Recommendations include strategic investment in tailored resources, infrastructure development to bridge the digital divide, flexible administrative policies, and fostering a collaborative learning environment that empowers teachers to enhance their pedagogical practices and, consequently, improve student English language proficiency.